Evaluating the association between unmet healthcare needs and subsequent clinical outcomes: protocol for the Addressing Post-Intensive Care Syndrome-01 (APICS-01) multicentre cohort study. Issue 10 (23rd October 2020) - Akhlaghi, Narjes; Needham, Dale M; Bose, Somnath; Banner-Goodspeed, Valerie M; Beesley, Sarah J; Dinglas, Victor D; Groat, Danielle; Greene, Tom; Hopkins, Ramona O; Jackson, James; Mir-Kasimov, Mustafa; Sevin, Carla M; et al.
Abstract : Introduction: As short-term mortality declines for critically ill patients, a growing number of survivors face long-term physical, cognitive and/or mental health impairments. After hospital discharge, many critical illness survivors require an in-depth plan to address their healthcare needs. Early after hospital discharge, numerous survivors experience inadequate care or a mismatch between their healthcare needs and what is provided. Many patients are readmitted to the hospital, have substantial healthcare resource use and experience long-lasting morbidity. The objective of this study is to investigate the gap in healthcare needs occurring immediately after hospital discharge and its association with hospital readmissions or death for survivors of acute respiratory failure (ARF). Methods and analysis: In this multicentre prospective cohort study, we will enrol 200 survivors of ARF in the intensive care unit (ICU) who are discharged directly home from their acute care hospital stay. Unmet healthcare needs, the primary exposure of interest, will be evaluated as soon as possible within 1 to 4 weeks after hospital discharge, via a standardised telephone assessment. The primary outcome, death or hospital readmission, will be measured at 3 months after discharge. Secondary outcomes (eg, quality of life, cognitive impairment, depression, anxiety and post-traumatic stress disorder) will be measured as part of 3-month and 6-month telephone-based follow-up assessments. Descriptive statistics will be reported for the exposure and outcome variables along with a propensity score analysis, using inverse probability weighting for the primary exposure, to evaluate the relationship between the primary exposure and outcome. Ethics and dissemination: The study received ethics approval from Vanderbilt University Medical Center Institutional Review Board (IRB) and the University of Utah IRB (for the Veterans Affairs site). These results will inform both clinical practice and future interventional trials in the field. We plan to disseminate the results in peer-reviewed journals, and via national and international conferences. Trial registration details: ClinicalTrials.gov (NCT03738774 ). Registered before enrollment of the first patient.